Pengembangan LKPD Mobile Learning Berbasis Android dengan Berbantuan Case Method untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa SMA di Kelas X - Fadlan Alkhairi; Tiur Malasari Siregar (Journal on Education, 2024)
This research aims to find out the validity, practicality and effectiveness of the media: LKPD Mobile Learning which was developed on an Android basis with the help of the case method to improve the problem solving abilities of high school students in Class X using the ADDIE model. This research was conducted at SMAS Methodist 7 Medan with the subjects being 20 class X students. Data analysis techniques were carried out using qualitative and quantitative data. For the start of this research, students in class used in learning. The research results obtained showed that the mobile learning LKPD developed based on Android with the help of the case method was declared “Very feasible” with a percentage of 98,85%. The mobile learning LKPD media which was developed on an Android basis with the help of the case method was declared “very practical” with a percentage of 96,6%. The LKPD mobile learning media developed on Android is said to be “Effective” with an N-Gain value of 0,5. Thus, it can be concluded that the development of Android-based Lkpd Mobile Learning with the help of the case method can improve the problem solving abilities of SMAS Methodits 7 Medan students.